The Mechanism of Warburg Effect-Induced Chemoresistance in Cancer - Liu, Chang; Jin, Ying; Fan, Zhimin (Frontiers in Oncology, 2021)
Although chemotherapy can improve the overall survival and prognosis of cancer patients, chemoresistance remains an obstacle due to the diversity, heterogeneity, and adaptability to environmental alters in clinic. To determine more possibilities for cancer therapy, recent studies have begun to explore changes in the metabolism, especially glycolysis. The Warburg effect is a hallmark of cancer that refers to the preference of cancer cells to metabolize glucose anaerobically rather than aerobically, even under normoxia, which contributes to chemoresistance. However, the association between glycolysis and chemoresistance and molecular mechanisms of glycolysis-induced chemoresistance remains unclear. This review describes the mechanism of glycolysis-induced chemoresistance from the aspects of glycolysis process, signaling pathways, tumor microenvironment and their interactions. The understanding of how glycolysis induces chemoresistance may provide new molecular targets and concepts for cancer therapy.